The wear performance of glazed and polished full contour zirconia - Alves, Larissa Marcia Martins [UNESP]; Contreras, Lisseth Patricia Claudio [UNESP]; Bueno, Mirian Galvão [UNESP]; Campos, Tiago Moreira Bastos; Bresciani, Eduardo [UNESP]; Valera, Marcia Carneiro [UNESP]; de Melo, Renata Marques [UNESP] (FapUNIFESP (SciELO), 2019)
This study evaluated the influence of zirconia surface finishes on the wear of an enamel analogue. 40 zirconia discs were divided into four groups: control (without finish); glazed; polished; polished and glazed. All samples were subjected to wear against steatite antagonists. The specimens underwent roughness, topographic, scanning electron microscopy (SEM) and wettability analyses. Quantitative wear measurements were performed on both steatites and discs. To measure wear of steatites the weight before and after the test and the diameter after the test were used. Profilometer measurements were performed to determine the wear on discs. Roughness, volumetric wear and mass loss were analyzed using the Kruskal-Wallis and Dunn tests (5%), while contact angle values were analyzed with One-way ANOVA and Tukey tests (5%). The polished group had the lowest roughness means, being statistically different from the other groups (p-value=0.0001). The glazed group presented the lowest steatite volumetric wear (p-value=0.0001), but not statistically different from the polished and glazed group, whereas these groups presented the highest zirconia volumetric wear, with statistically different (p-value=0.0002) compared to the others. SEM showed irregularities on the control groups surface, grooves on the polished group, and a homogeneous surface for the glazed group with a few pores. All groups presented contact angles lower than 90 degrees, characterizing hydrophilic surfaces. It can be concluded that just glazed zirconia caused less wear on the antagonist when compared to no finish and polished zirconia.
Keywords: Ceramics; Dental materials; Dental restoration wear; Zirconium